2022
DOI: 10.3389/fnins.2022.882996
|View full text |Cite
|
Sign up to set email alerts
|

Intracerebral Hemorrhage-Induced Cognitive Impairment in Rats Is Associated With Brain Atrophy, Hypometabolism, and Network Dysconnectivity

Abstract: The mechanisms underlying intracerebral hemorrhage (ICH)-related cognitive impairment (CI) remain unclear. Long-term structural and functional changes were investigated in the brains of healthy male and female Wistar rats after experimental ICH. Following double injection of autologous blood, rats underwent short-term (onset, 3 and 7 days) and long-term (3 and 6 months) radiological assessment and behavioral tests exploring spontaneous locomotion, anxiety-like behavior and working memory, spatial recognition m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 28 publications
1
2
0
Order By: Relevance
“…The specific number of dead rats in each group and the time of death are presented in Table 2 . The results were consistent with the ICH model death of SD rats approved by the national Ethical Committee in Animal Experimentation (CEEA, Comité d’Ethique en Experimentation Animale), from the French Ministry for Education and Research [ 29 ]. Due to ICH modeling, 24 rats perished.…”
Section: Resultssupporting
confidence: 84%
See 1 more Smart Citation
“…The specific number of dead rats in each group and the time of death are presented in Table 2 . The results were consistent with the ICH model death of SD rats approved by the national Ethical Committee in Animal Experimentation (CEEA, Comité d’Ethique en Experimentation Animale), from the French Ministry for Education and Research [ 29 ]. Due to ICH modeling, 24 rats perished.…”
Section: Resultssupporting
confidence: 84%
“…ICH results in a complex mechanism of central nervous system injury, including both physical injury and primary injury as a result of hematoma formation. Secondary injury primarily arises from microglial activation, mitochondrial dysfunction, and the release of toxic neurotransmitters and inflammatory mediators [29]. As crucial innate immune cells, microglia serve as the brain's sentinels and are believed to be the first non-neuronal cells to respond to acute brain injury [31][32][33].…”
Section: Discussionmentioning
confidence: 99%
“…In a microhemorrhage model in mice, changes in long-term cognitive activities, such as a reduction in visual recognition memory, were observed, 39 but not in spontaneous motor activity, while another work has shown that neuromotor changes can occur 3 days after the hemorrhagic insult. 40 …”
Section: Discussionmentioning
confidence: 99%